FROMULATION AND EVALUATION OF HERBAL ANTIMICROBIAL CREAM OF CLITORIA TERNATEA FLOWER - Kale Priti Rohidas,; Palve Aniket Rajendra,; Gulme Vivek Rajendra,; Keskar Sushant Sunil,; Atole Samiksha Nitin,; Sake Vaishnavi Sanjay,; Dr. Khedkar Amol Navnath, (The Bioscan, 2026)
The present study focuses on the formulation and evaluation of an antimicrobial cream containing extract of Clitoria ternatea flower. Herbal formulations have gained significant attention due to their safety, effectiveness, minimal side effects, and natural origin. Clitoria ternatea is well known for its antimicrobial, antioxidant, anti-inflammatory, and wound-healing properties because of the presence of phyto-constituents such as flavonoids, tannins, alkaloids, glycosides, and anthocyanins. The aim of the study was to develop a stable and effective topical antimicrobial cream using Clitoria ternatea flower extract and to evaluate its pharmaceutical parameters. The antimicrobial cream was prepared by using suitable ingredients such as stearic acid, cetyl alcohol, glycerin, triethanolamine, preservatives, and purified water by the oil-in-water (O/W) emulsification method. The prepared formulation was evaluated for various physicochemical parameters including color, odour, appearance, homogeneity, pH, spreadability, washability, viscosity, stability, and antimicrobial activity. The pH of the cream was found to be compatible with skin pH, indicating suitability for topical application. The formulation showed good consistency, smooth texture, and satisfactory spreadability without causing irritation. The study concludes that Clitoria ternatea flower can be effectively incorporated into a topical cream formulation with good antimicrobial potential and acceptable pharmaceutical properties.